Peptide-Based Bioinspired Approach to Regrowing Multilayered Aprismatic Enamel - Mukherjee, Kaushik (ACS Omega, 2018)
[Image: see text] The gradual discovery of functional domains in native enamel matrix proteins has enabled the design of smart bioinspired peptides for tooth enamel mimetics and repair. In this study, we expanded upon the concept of biomineralization to design smaller amelogenin-inspired peptides with conserved functional domains for clinical translation. The synthetic peptides displayed a characteristic nanostructured scaffold reminiscent of ‘nanospheres’ seen in the enamel matrix and effectively controlled apatite nucleation in vitro resulting in the formation of smaller crystallites. Following application of the peptides to sectioned human molar teeth, a robust, oriented, synthetic aprismatic enamel was observed after 7 days of incubation in situ. There was a two-fold increase in the hardness and modulus of the regrown enamel-like apatite layers and an increase in the attachment of the tooth-regrown layer interface compared to control samples. Repeated peptide applications generated multiple enamel-like hydroxyapatite (HAP) layers of limited thickness produced by epitaxial growth in which c-axis oriented nanorods evolved on the surface of native enamel. We conclude that peptide analogues with active domains can effectively regulate the orientation of regenerated HAP layers to influence functional response. Moreover, this enamel biofabrication approach demonstrates the peptide-mediated growth of multiple microscale HAP arrays of organized microarchitecture with potential for enamel repair.